Percutaneous transvenous balloon mitral valvuloplasty: mid-term results in adolescents - Ünal, Nurettin; Meşe, Timur; Hüdaoğlu, Suphi; Çelikkol, Bilge; Yunus, Şemsettin; Saylam, Gül Sağın; Akçoral, Adnan (The Turkish Journal of Pediatrics, 1999)
Six patients with mitral valve stenosis underwent percutaneous balloon mitral valvuloplasty (PBMV) in our department between November 1992 and December 1997. Five patients had rheumatic mitral valve stenosis and one had congenital mitral valve stenosis and Eisenmenger’s syndrome with patent ductus arteriosus (PDA). Functional status before PBMV was class IV in two patients, class III in two patients, and class II-III in two patients, as classified by the New York Heart Association (NYHA). The mean diastolic pressure gradient across the mitral valve measured during heart catheterization before and immediately after PBMV was 18.8 ± 10.42 and 9.4 ± 7.7 mmHg, respectively ( p < 0.01 ). The patients were followed for a mean period of 36.6 ± 8.5 months (range 12 to 72 months) after the procedure. During follow-up, post PBMV mean diastolic transmitral gradient measured by color Doppler echocardiography decreased from 19.3 ± 11.16 to 7.43 ± 7.3 mmHg ( p < 0.01 ) and the mitral valve area increased from 1.09 ± 0.7 to 3.1 ± 0.9 cm² ( p < 0.002 ). Functional capacity showed improvement to NYHA class I in four patients, to class II-III in the patient with congenital mitral valve stenosis and Eisenmenger’s syndrome with PDA and to class II in one patient with severe mitral valve calcification in whom restenosis occurred three years after PBMV. Percutaneous balloon mitral valvuloplasty PBMV can achieve very good short- and mid-term results in relieving symptomatic rheumatic mitral valve stenosis.